The model of community empowerment in fire forest disaster prevention in Indonesia - Yusuf, Husmiati; Fahrudin, Fahmi Ilman; Fahrudin, Adi; Huraerah, Abu; Wanda, Kiyah George Albert (Technium Sustainability, 2022)
This paper will look into the topic of community involvement in forest fire disaster prevention, specifically in Indonesia. To begin, the paper will discuss the problem of forest fires in Indonesia, which occur frequently. The study also addressed issues related to disaster management, such as a lack of competence and knowledge, which resulted in disaster management ineffectiveness. The paper's third portion discusses the government's involvement in catastrophe management. Several initiatives and support have been implemented.